PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA STUDIO RIBKA FOTO CABANG SEKIP DI PALEMBANG - Febri Yanti; Azizah Karim; Muhammad Wadud (Universitas Indo Global Mandiri)
The service quality ofo needs fulfillment, consumers desire, and its provison accuracy to meet consumers expectation. using the method of quantitative statistical research and data analysis techniques used was simple linear regression analysis.Since t-count (11,505)> (2,368) and significant value (0,000) <(0,01). Wasmeansthe HO was rejected and Ha was accepted, then the service qualty significantly influence consumers satisfaction at Studio Ribka Photo Sekip branch in Palembang. Then, correlation and determination test where they were obtained correlation coefficient value of R = 0,598 which means that the correlation between service quality and consumers satisfaction was very strong that was 59,8%. After the correlation test was applied, it was followed by determination test. Determination test was done to see how much the contribution of variable x to variable y, where obtained value of was R2 0,593. It could be stated that the independent variabel correlation between the service quality and consumers statisfaction was 59,3%, meanwhile the rest was 41,7% explained by other variable product, price, promotion, place, presentasi and personalia. Keywords: Service Quality, Consumers Satisfaction, Quantitative methods